Peran Dan Strategi Pemerintah Daerah Dalam Mencegah Penyalahgunaan Narkotika Di Kalangan Remaja - Heriyanto Heriyanto (LPPM Universitas Sains dan Teknologi Komputer, 2023)
Adolescence is a stage for someone to become an adult who has a high curiosity so that he is at risk of being easily influenced. The BKKBN defines youth as someone who is between the ages of 10 and 24, and it is at this stage that adolescents experience many changes in themselves, starting from their bodies, minds, emotions, to how they get along and socialize with their environment. So that it is not uncommon to find teenagers who are wrong in socializing, they can fall into the use of illegal drugs (narcotics). Throughout 2022 BNN recorded 851 cases which in percentage terms experienced an increase of 11.1% from 2021 of 766 cases. When viewed from the age of users, they are aged 15-35 years with a percentage of 82.4% as users, 47.1% as dealers and 31.4% as couriers. Of course this is very concerning for future generations of the Indonesian nation. From the results of this research article about the role of local government in overcoming narcotics abuse, it is very important to prevent and combat narcotics among adolescents. Among the good things that local governments can do in overcoming the above problems are, first, the government must be able to take an attitude and policy that fighting narcotics is a joint task, not just the National Narcotics Agency, so that it can put pressure on every agency to close the space for movement against narcotics. only include it in the school curriculum at every level, second, local governments can promote the development of positive alternatives for youth to avoid drug abuse. And third, promotive and preventive strategies are the most successful and fundamental approaches to avoiding and eliminating drug use among adolescents. The latter is repression as the most realistic and practical effort, while treatment and rehabilitation are the most humane.